Strategi Pendidikan Literasi Agama Islam Melalui Digitalisasi Dakwah Berbasis Media Sosial di Era Industri 4.0 - Ardiansyah, Adistya Eka Sis (Matan : Journal of Islam and Muslim Society, 2025)
The advancement of digitalization requires da'wah activities and Islamic literacy to adapt to these developments. This research aims to describe the strategy of developing Islamic literacy through digitalising social media-based da'wah. The method in this research applies a literature study approach in the form of qualitative research; the data sources used are various books and relevant literature. The results of this study indicate that 1) the concept of Islamic literacy is an effort to involve the ability to read, write, think critically, to implement values derived from Islamic rules. 2) The concept of digitalization of da'wah through social media provides easy access and dissemination of da'wah messages. 3) Supporting factors for the digitalization of da'wah is the wider scope of dissemination of da'wah content and the growth of internet users. Then, the inhibiting factors are the lack of knowledge and equipment needed to create digital media content, limited devices and internet access. 4) Strategies that can be applied are structured planning, choosing the right digital media, forming a media team, identifying supporting and inhibiting factors, and increasing digital literacy.